Konkurenčni izzivi globalizacije trgov za slovenska podjetja - Jurše, Milan (Akademija MM, 1998)
Paper discusses the globalization process in international markets and its implication for international marketing management. Recent development in international financial markets signal the increased interdependencies and interconnectedness of national economies and international markets, and directly affect also international markets and marketing strategies of firms in their effort to build desired market position in international markets. In the paper some influences of the globalisation of markets on the Slovene companies are presented and their possible marketing responses discussed.
Keywords: konkurenčnost; mednarodni marketing; mednarodno trženje; strategija trženja; zunanja tržišča